Etiopathogenesis of Sheehan’s Syndrome: Roles of Coagulation Factors and TNF-Alpha - Halit Diri; Elif Funda Sener; Fahri Bayram; Nazife Tascioglu; Yasin Simsek; Munis Dundar (International Journal of Endocrinology)
Sheehan’s Syndrome (SS) is defined as pituitary hormone deficiency due to ischemic infarction of the pituitary gland as a result of massive postpartum uterine hemorrhage. Herein, we aimed to investigate the roles of Factor II (G20210A), Factor V (G1691A), MTHFR (C677T and A1298C), PAI-1 4G/5G, and TNF-α (-308  G>A) gene polymorphisms in the etiopathogenesis of SS. Venous blood samples were obtained from 53 cases with SS and 43 healthy women. Standard methods were used to extract the genomic DNAs. Factor II (G20210A), Factor V (G1691A), and MTHFR (C677T and A1298C) polymorphisms were identified by real-time PCR. PAI-1 4G/5G and TNF-α (-308  G>A) gene polymorphisms were detected with polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) methods. According to statistical analysis, none of the polymorphisms were found to be significantly higher in the SS group compared to the control group. Hence, we suggest that genetic factors other than Factor II, Factor V, MTHFR, PAI-1, and TNF-α gene polymorphisms should be researched in the etiopathogenesis of SS.